Akuntabilitas Pondok Pesantren dalam Konsep Amar Ma’ruf Nahi Munkar - Firdausi, Indira Cahyaning; Amin, Muhammad Al (Universitas Muhammadiyah Magelang, 2021)
This study aims to analyze the accountability of An-Najach Islamic boarding school in the of amar ma'ruf nahi munkar concept. This study also aims to determine the application of Islamic values at each stage of accountability. The method used in this research is a qualitative research methodology with a phenomenological approach. The results show that accountability at the An-Najach Islamic Boarding School has been implemented with transparency and the application of Islamic values even though the financial reporting is still simple and not in accordance with the Financial Accounting Standards for Entities without Public Accountability (SAK ETAP) which is used as a reference in preparing reports. finance. Islamic boarding school. Accountability at the An-Najach Islamic Boarding School also reveals that the accountability of the pesantren prioritizes the principles of trust and honesty within the framework of amar ma'ruf nahi Munkar.